(untitled) (Journal of Plant Disease Sciences, 2020)
Rapid roving survey of citrus nurseries was undertaken during 2016-2018 in Amravati district of Central India to assess and characterize Phytophthora spp. in major citrus growing areas. P. nicotianae var. parasitica was found most prevalent species amongst three species of Phytophthora in study area. Molecular study of eight selected isolates revealed that universal primers ITS1 and ITS 4 were shown amplification at 800bp for all isolates that is confirmed as Phytophthora. In cultural studies growth of aggressive Phytophthora isolate was compared on five culture media’s with and without addition of PARPH antibiotics. The radial mycelial growth of highly aggressive, predominant and highly sporulating Phytophthora spp. i.e. Phytophthora nicotianae var. parasitica was compared on different culture media at 7, 9 and 11 days after inoculation (DAI). Corn Meal Agar (CMA) and V8 juice was the most suitable medium for the growth of Phytophthora and fungus grow faster on CMA.